Perbandingan Koefisien NMF dan Proyeksi Bilinear Space Sebagai Fitur pada Pengenalan Ekspresi Wajah Manusia - William Salim (Bina Nusantara University, 2012)
NMF is one new developed method to make the part-based representation of non-negative data, such as human face image. NMF can reduce the dimension of high dimensional data such as multimedia data. In many researches,NMF can also used as a classification technique done by utilizing the extracted feature through NMF process. This article discusses about the classification technique of human face expression using NMF. This is done using NMF coeffisient and bilinear projection of face image. Some researches show the use of NMF coefficient in classification and some others use bilinear space projection. This research is conducted by simulating face espression recognition to the two available approaches and then comparing the accuracy and time efficiency aspect of the two methods. Through this research, it can be concluded that the use of NMF coefficient results in better accuracy compared to bilinear space projection, but bilinear space projection obtains better time efficiency.